2024
DOI: 10.1097/corr.0000000000003033
|View full text |Cite
|
Sign up to set email alerts
|

Are Quality Scores in the Centers for Medicaid and Medicare Services Merit-based Incentive Payment System Associated With Outcomes After Outpatient Orthopaedic Surgery?

Derek T. Schloemann,
Danielle M. Wilbur,
Paul T. Rubery
et al.

Abstract: Background The Medicare Merit-based Incentive Payment System (MIPS) ties reimbursement incentives to clinician performance to improve healthcare quality. It is unclear whether the MIPS quality score can accurately distinguish between high-performing and low-performing clinicians. Questions/purposes (1) What were the rates of unplanned hospital visits (emergency department visits, observation stays, or unplanned admissions) within 7, 30, and 90 days of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…One large study [1] evaluated 3.4 million patients cared for by 80,000 primary care physicians and showed that 19% of physicians with low MIPS scores had composite outcomes performance metrics in the top quintile, while 21% of physicians with high MIPS scores had outcomes in the bottom quintile. This corroborates the findings of our featured article in CORR ® , in which Schloemann and colleagues [6] found only a small association between MIPS quality scores for individual physicians and the risk of an unplanned hospital visit after outpatient orthopaedic surgery, and that these visits consisted mostly of trips to the emergency department.…”
Section: Derek Schloemann MD Mphssupporting
confidence: 90%
See 2 more Smart Citations
“…One large study [1] evaluated 3.4 million patients cared for by 80,000 primary care physicians and showed that 19% of physicians with low MIPS scores had composite outcomes performance metrics in the top quintile, while 21% of physicians with high MIPS scores had outcomes in the bottom quintile. This corroborates the findings of our featured article in CORR ® , in which Schloemann and colleagues [6] found only a small association between MIPS quality scores for individual physicians and the risk of an unplanned hospital visit after outpatient orthopaedic surgery, and that these visits consisted mostly of trips to the emergency department.…”
Section: Derek Schloemann MD Mphssupporting
confidence: 90%
“…Dr. Manner: As part of your conclusion, you recommend that MIPS be "modified to more strongly link reimbursement to risk-adjusted patient outcomes, thereby better-aligning incentives between patients, surgeons, and CMS" [6]. What suggestions might you provide on how to do that?…”
Section: Derek Schloemann MD Mphsmentioning
confidence: 99%
See 1 more Smart Citation